تأثير إضافة مستويات مختلفة من ماء الجفت وهيومات البوتاسيوم إلى طبقة التربة تحت السطحية في منحنيات الشد الرطوبي والثوابت الهيدروديناميكية لهذه الطبقة (Journal of Hama University, 2024)
The research was carried out in the fall season on silty clay soil at the Center of Scientific Agricultural Research in Latakia (Settkhiris Station) in 2019. The study included nine treatments (W0H0 control without mechanical dismantling and without adding, W0H1 adding potassium humate at a concentration of 1 kg/dunum only during mechanical dismantling of the subsoil layer, W0H2 adding potassium humate at a concentration of 2 kg/dunum only during the mechanical dismantling of the subsurface soil layer, W1H0 adding (OMW) at a concentration of 2 liters/m2 only during the mechanical dismantling of the subsurface soil layer, W1H1 adding (OMW) at a concentration of 2 liters/m2 and potassium humate at a concentration of 1 kg / dunum during the mechanical dismantling of the subsurface soil layer, W1H2 adding (OMW) at a concentration of 2 L/m2 and potassium humate at a concentration of 2 kg / dunum during the mechanical dismantling of the subsurface soil layer, W2H0 (OMW)at a concentration of 4 L/m2 only during the mechanical dismantling of the subsurface soil layer, W2H1 Adding (OMW)at a concentration of 4 liters/m2 and potassium humate at a concentration of 1 kg/dun during the mechanical dismantling of the subsurface soil layer, W2H2 Adding (OMW) at a concentration of 4 liters/m2 and potassium humate at a concentration of 2 kg/dun during the mechanical dismantling of the subsurface soil layer). The results showed that the moisture content of the soil before pF3 is higher in the treatments to which (OMW) and potassium humate were added, especially at the higher levels of W2H2 addition. However, the moisture content of the soil after pF3 is higher in the control treatment, and this is due to a change in the distribution of the porous system in the soil. The value of the constants (a and b) also increased by 0.23484 and 3.278 respectively in the W2H2 treatment compared to the control. This is considered a good indicator of greater water availability to the plant for the treatments to which (OMW) and potassium humate were added at the same moisture tension value. The percentage of available water increased by 4.4% by volume in the W2H2 treatment compared to the control. Therefore, it is recommended to add (OMW) and potassium humate according to the W2H2 treatment to increase the percentage of water available to the plant for clay soils similar to the studied soil, and to continue research on other types of soils.